Caregiver factors that contribute to development of complications in disabled children in Elim Hospital, Vhembe District of Limpopo Province in South Africa - Mulugo, Naledzani Rosemary (University of Limpopo, 2016)
Background: Disabled children with different conditions such as cerebral palsy, traumatic brain injuries, developmental delays, severe orthopaedic impairment, hydro and micro-cephalous are brought to Elim Hospital for rehabilitation therapy. Most of these disabled children stay with caregivers who are responsible for their care including rehabilitation therapy at home to avoid complications. The aim of the study was to establish factors that contribute to development of complications in disabled children. Methods: The quantitative descriptive study design was used and convenience sampling method was used to select 52 caregivers out of the population of 60. Questionnaires and observation checklist were used for data collection at the rehabilitation therapy clinic during their rehabilitation therapy visit. Data were analysed using SPSS version 22. Results: The results show that there is no association between diagnosis and the development of complications. There was an association between availability of resources which is one of the caregiver factors and the development of complications. Conclusion: The study concludes that, availability of resources to provide the rehabilitation therapy on the disabled children is the contributing caregiver factors on the development of complications in disabled children at Elim Hospital.
Thesis (MPH.) -- University of Limpopo, 2016
Keywords: Caregivers; Disabled children; Handicapped children--South Africa-Limpopo; Caregivers--South Africa-Limpopo; Neurology